Epidemiology of hepatocellular carcinoma - Paraná, Raymundo; Almeida, Delvone (Iatreia, 2007)
The incidence of hepatocellular carcinoma (HCC) has increased both due to the worldwide increase on the virus C infection and to the increase on the survival rate of patients with chronic liver disease. It usually is an aggressive tumor with survival rate directly associated with the hepatic residual liver function as well as the size of the tumor at the diagnosis.